2004
DOI: 10.4049/jimmunol.173.10.5935
|View full text |Cite
|
Sign up to set email alerts
|

Replication-Dependent Potent IFN-α Induction in Human Plasmacytoid Dendritic Cells by a Single-Stranded RNA Virus

Abstract: Plasmacytoid dendritic cells sense viral ssRNA or its degradation products via TLR7/8 and CpG motifs within viral DNA via TLR9. Although these two endosomal pathways operate independently of viral replication, little is known about the detection of actively replicating viruses in plasmacytoid dendritic cell (PDC). Replication and transcription of the viral genome of ssRNA viruses as well as many DNA viruses lead to the formation of cytosolic dsRNA absent in noninfected cells. In this study, we used human respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
177
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(192 citation statements)
references
References 46 publications
14
177
1
Order By: Relevance
“…Macrophages can be infected in cell culture, 17 so this may represent actual infection, but it is also possible that this represents phagocytosed antigen. Although DCs can be infected with RSV in vitro 18 and CD1a þ cells were detected in peribronchiolar tissue, no RSV-positive cells were identified that appeared to have DC morphology. DCs are highly mobile and, if infected, may have already moved to areas of organized lymphoid tissue for induction of adaptive immune responses.…”
Section: Discussionmentioning
confidence: 96%
“…Macrophages can be infected in cell culture, 17 so this may represent actual infection, but it is also possible that this represents phagocytosed antigen. Although DCs can be infected with RSV in vitro 18 and CD1a þ cells were detected in peribronchiolar tissue, no RSV-positive cells were identified that appeared to have DC morphology. DCs are highly mobile and, if infected, may have already moved to areas of organized lymphoid tissue for induction of adaptive immune responses.…”
Section: Discussionmentioning
confidence: 96%
“…[18][19][20] It has been reported that replication and transcription of the viral genome of single-stranded viral RNA viruses and many DNA viruses often lead to the formation of cytosolic dsRNA. 45,46 Thus, dsRNA could induce PKR activation. Recently, 2AP was suggested to have suppressive effect on other kinases; 47 therefore, further studies to explore the roles of PKR and other kinases in VZV infection are needed.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that RSV infection triggers type I IFN induction in pDCs in a MyD88-independent manner. 75 This induction is entirely dependent on virus entry into cytosol and replication. Furthermore, while pDCs recognize HSV-1 genomic DNA via TLR9, there is no increase in HSV-1 replication in TLR9-deficient mice after local infection.…”
Section: Recognition Of Viral Components By Non-tlr Sensorsmentioning
confidence: 99%